The Effect of Technological Complexity (KT) and Compatibility (KOM) on The Sustainability of The Green and Smart Port Concept (CTU): TAM Extended Approach Case Study at Teluk Lamong Terminal, A Subsidiary of PT Pelindo III - Reka Yusmara Mardiputra; Kusuma Ratnawati; Ananda Sabil H (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
This study examines and analyzes the relationship between the technological complexity (KT) and compatibility (KOM), to a continuance to use (CTU) of green and smart port concepts using TAM theory extended. Adding technological complexity and compatibility as an external factor into TAM in terms of perceived usefulness (PU) and perceived ease of use (PEOU) that affect continuance to use green and smart concepts. This study uses a survey method. It is distributed to owners/operational/invoicing managers of Terminal Teluk Lamong (TTL) Customers (Shipping Company, Forwarding, Trucking Company) in Surabaya, Indonesia. The sampling technique is using Slovin's formula with 304 respondents. The data analysis technique uses SEM (Structural Equation Modelling) with SMART PLS 3.0. Both KT and KOM have a significant effect on PU and PEOU. Both PU and PEOU have a significant effect on CTU, and PEOU has a significant effect on PU. This research was conducted at TTL, the only terminal in Indonesia that uses the green and smart port concept. There is no comparison with other terminals in Indonesia on the implementation of the green and smart port concept. Especially for shipping companies, respondents cannot reach owner/principal/shareholders due to Indonesian government policy that international Shipping Companies are not allowed to open branches independently. However, they have to cooperate with local companies (agents). Port Industries (TTL) can develop an appropriate marketing strategy based on this research's results. Technological complexity and compatibility have a significant effect on the continuance to use GSP. Management of TTL has to consider technology and operational systems development with a low-level complexity and according to customer's needs. This research contributes to enrichment and extending TAM theory in terms of green and smart port concept sustainability. Not only affected by PU and PEOU but technological complexity (KT) and Compatibility (KOM) factors are important.